История Окраин Республики Польши в XX веке. Информационное сообщение о деятельности большевицко-украинских факторов на территории Польши и Совдепии = Istoriya Okrain Respubliki Pol'shi v XX veke. Informatsionnoye soobshcheniye o deyatel'nosti bol'shevitsko-ukrainskikh faktorov na territorii Pol'shi i Sovdepii - ROGUSKI, Rafał (Historia i Świat, 2017)
Presented text concerns actions of the security services of Soviet Ukraine against Poland during the election to the polish Parliament in 1922. It shows the actions of sabotage groups, spies and political bodies of Soviet Ukraine. The article discusses state of safety polish – soviet borderland on the section of Eastern Malopolska not yet joined to Poland. It shows some methods of intelligence work and the organization of sabotage activities in Poland.